2022
DOI: 10.3389/fmicb.2022.984801
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in the structures and biological activities of secondary metabolites from Talaromyces

Abstract: The genus Talaromyces belongs to the phylum Ascomycota of the kingdom Fungi. Studies have shown that Talaromyces species yield many kinds of secondary metabolites, including esters, terpenes, steroids, alkaloids, polyketides, and anthraquinones, some of which have biological activities such as anti-inflammatory, bacteriostatic, and antitumor activities. The chemical constituents of fungi belonging to the genus Talaromyces that have been studied by researchers over the past several years, as well as their biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Talaromyces contains over 200 secondary metabolites, including esters, terpenes, steroids, alkaloids, polyketides, and anthraquinones [ 17 ]. Some compounds have biological activities, such as anti-inflammatory, bacteriostatic, and antitumor activities [ 18 ]. The compounds of Talaromyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Talaromyces contains over 200 secondary metabolites, including esters, terpenes, steroids, alkaloids, polyketides, and anthraquinones [ 17 ]. Some compounds have biological activities, such as anti-inflammatory, bacteriostatic, and antitumor activities [ 18 ]. The compounds of Talaromyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…The fungus Talaromyces , which is broadly dispersed in the natural environment (Zhang K. et al, 2022 ), demonstrates significant potential as a biological resource in food industry, ecology, agriculture, and medicine (Nicoletti et al, 2018 ; Devi et al, 2020 ; Prieto et al, 2021 ; Yadav et al, 2022 ; Aggarwal et al, 2023 ; De Eugenio et al, 2023 ; Xue et al, 2023 ). To further understand its characteristics, the biosynthetic pathways, biological activity (Chen et al, 2022 ; Lei et al, 2022 ; Lv et al, 2023 ; Nicoletti et al, 2023 ), and structure–activity relationship (Xie et al, 2022 ; Zhang M. et al, 2022 ) in Talaromyces have been extensively probed. These studies have also shown that Talaromyces exhibits numerous beneficial bioactivities and exceptional biosynthetic capabilities, which makes it suitable for wide-ranging industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Talaromyces has the capability to produce novel secondary metabolites with potent biological activities (Lei et al, 2022 ), such as antimicrobial depsidone (talaronin E) (Nicoletti et al, 2023 ) and polyketide (tanicutone B) (Wang et al, 2023 ), cytotoxic cytochalasan (talachalasin A) (Ding et al, 2023 ), dimeric oxaphenalenone aminoglycoside (glyclauxin D) (Samarasekera et al, 2023 ), antiviral cytochalasan (talachalasin B) (Ding et al, 2023 ), anti-inflammatory α-pyrone derivative (talarolactones E and F) (Li et al, 2023 ), phthalides (amestolkins A and B) (Huang et al, 2023 ), and insecticidal alkaloid (talaroenamine D) (Zang et al, 2015 ). Therefore, Talaromyces can be used to synthesize novel compounds (Kumari et al, 2018 ; Lan and Wu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi of the genus Talaromyces (Trichocomaceae) are important due not only to their ubiquitous nature, as they can be isolated from soil, plants, marine organisms and foods, but also to their great potential in agricultural applications as biological control agents [ 1 ] and to degrade agricultural waste [ 2 ]. Moreover, Talaromyces species also produce a variety of specialized metabolites such as alkaloids, peptides, polyketides, quinones, steroids and terpenoids, some of which exhibited relevant biological and pharmacological activities [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%